Ekonomizm nauk o zarządzaniu a przedsiębiorczość personalistyczna - Bombała, Bronisław (Annales. Etyka w Życiu Gospodarczym, 2013)
The article presents the view that the introduction of the personalistic paradigm into entrepreneurship will enable integral economic growth and remove the causes of today’s crisis, that is economism and instrumental rationality. Personalism, which recognizes man as a conscious person experiencing self and others, has special qualities for application. This is the most useful approach to philosophical and ethical analysis of the modern enterprise. In this article the focus is on a company managed according to personalistic ethics. Entrepreneurship in the personalistic approach is the art of management, which increases the area of common good.